Aktualisasi Nilai Siri’ Na Pacce Pada Masyarakat Suku Bugis-Makassar Di Kecamatan Rappocini Kota Makassar Provinsi Sulawesi Selatan - Nurazizah Rahmi R; Yadi Ruyadi; Wilodati (Faculty of Social Science, Universitas Negeri Malang, 2025)
The Bugis-Makassar tribe has a strong life principle, Siri’ na Pacce, which is interpreted as self-esteem and is highly sensitive, making it forbidden for them to remain silent if they are harassed or hurt. In its actualization, Siri’ Na Pacce often undergoes a shift in meaning that does not align with reality, triggering conflicts due to misunderstandings. This study aims to examine how the value of Siri’ Na Pacce is applied by the Bugis-Makassar community in Rappocini District, Makassar City, South Sulawesi Province. The research method used is a mixed method with a concurrent triangulation approach.The study involved 100 respondents aged 20-54 years from Rappocini District, determined using the Slovin formula (10%tolerance). Qualitative data were obtained through interviews with the community, Bugis-Makassar community leaders, and local police. Quantitative data analysis was performed descriptively and statistically, while qualitative data analysis involved data collection, data reduction, data presentation,and conclusion drawing. The research results indicate that the actualization of siri’ and pacce falls into three categories: siri’ that directs the arrangement of group life; siri’ that harms individuals or groups; and siri’ that triggers criminal acts. Quantitatively, the shift in Siri’ Na Pacce values significantly influences criminal acts by 52.1%. Qualitative findings indicate that the category of siri’ leading to criminal consequences is often influenced by gender, where women are vulnerable sources of siri’ and men take action, generally assault due to infidelity/adultery, to cover it.